Rapid Prototyping in Pakistan: A Technical Feasibility Study with Analytical Hierarchy Process Analysis, Bridging Civil and Industrial Engineering Perspectives - Ghulam Ameer Mukhtar; Sana Shehzadi; Muhammad Moazzam Ali; Abdul Ahad Malik; Muhammad Mohsin Arshad (Engineering Proceedings)
This study investigates the prospect of using rapid prototyping, particularly additive manufacturing, in Pakistan’s construction and manufacturing sectors, aiming to encourage R&D by the analysis of technical feasibility of this technology and collaboration between civil and industrial engineering. To solve this puzzle, we collected data from field experts, academia researchers, and license holders of this technology. Further, analytical hierarchy process (AHP), a sub-branch of multicriteria decision-making method (MCDM), was used to gauge the systematically by prioritizing selection criteria for solving the problem. AHP makes the methodical process more accurate and organized, which helped us to proposed a feasibility study for the technology’s success in Pakistan’s construction and manufacturing industries. The findings show a 79.4% probability, which indicates interaction among both engineering disciplines. Furthermore, a sensitivity analysis was conducted to enhance the dependability of the AHP model, which assists in sound decision making during ambiguous conditions. Apart from economic technical aspects, sustainability plays a very crucial role in the evaluation process. This text shows the environmental effects and sustainability implications associated with the assimilation of rapid prototyping technologies. This supports the integration of rapid prototyping in Pakistan, contributing to discussions on technological innovations in emerging nations. This will also lay a foundation for future interdisciplinary collaboration and technological enrichments in both engineering domains.